THE POTENTIAL OF INTERLEUKIN 17 AS A PROGNOSTIC BIOMARKER AND A TARGET OF THERAPEUTIC MODALITIES IN ATOPIC DERMATITIS - Kardiana Purnama Dewi (Atma Jaya Catholic University of Indonesia, 2022)
Background. Atopic dermatitis (AD) is one of the most common chronic relapsing inflammatory skin disease. AD causes negative impacts on social and economic, especially on the patients’ and their families’ quality of life. The immune dysregulation in AD resulting in disruption of keratinocyte barrier and inflammation AD recently was associated with the response of TH17, which produce IL-17. This study aims to investigate the correlation of IL-17 with severity of AD. Methods. This retrospective cohort study was conducted in dermatovenerology outpatient department. Consecutive sampling was done during the period of the study on patients aged more than 14 years old diagnosed with AD. Demographic data, Scoring for AD (SCORAD) index, stress score, onset and duration of disease, and three mililitres of whole blood in vacutainer were obtained. IL-17 serum level analysis was measured on the blood by ELISA technique according to manufacturer’s protocol. P-value smaller than 0.05 was appraised as statistically significant. Results. There were significantly higher IL-17 serum level in AD patients compared with control patients. There were higher IL-17 serum level in moderate-severe compared to mild AD patients. There were also significantly longer in the duration of the disease and higher SCORAD index in moderate-severe compared to mild AD patients. There was very strong positive correlation between IL-17 serum level and SCORAD index. Conclusions. The findings of this study emphasize the potency of IL-17 as prognostic biomarkers and also as the potential target of therapeutic modalities.